PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS SMP NEGERI 4 SIAK HULU - Astuti, Puji; ', Zulkarnain; ', Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students’ achievement in learning mathematics especially grade VII4 of SMP Negeri 4 Siak Hulu under the Mastery Minimum Criteria with percentage of 35,14% on the test about integer and fractional. This research aims to improve the learning process and improve learning result in mathematics ingrade VII4  of SMP Negeri 4 Siak Hulu by implementation of inquiry learning strategy. This research is a class action research.  The subject of this research were the students in the class VII4  of  SMP Negeri 4 Siak Hulu that consist of 19 boys and 18  girls at the first  semester of academic year 2016/2017. The instruments of data collection in this research were observation sheets and student’smathematic tests. The observation sheets were analyzed in desciptive narative, while the student’smathematic tests were analyzed in statistic desciptive. The descriptive narative showed an improvement of  learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning mathematic from the basic score with percentage 35,14 % to 45,95% on the first test and 64,87% on second test. Based on the result of this research could be concluded that the implementation of inquiry learning strategy can improve the learning process and improve the student’s achievement of learning mathematic in grade VII4  of SMP Negeri 4 Siak Hulu in the first semester academic years 2016/2017.